Evaluations of A Bibliography of Periodicals Published in Ankara 1923-2015 - Selahattin Öztürk (Türk Kütüphaneciliği)
The quality of a research depends on the access of the accurate information. Bibliographies are the most important tools to provide this access. Therefore, the data in the bibliographies must be as detailed as possible and consist of consistent and accurate information. The amount of information in the publication named “A bibliography of periodicals published between 1923 and 2015 in Ankara” were examined in terms of its accuracy and order. All the deficiencies identified in the publication were assessed under general headings, rather than by individual examples; a short proposal and solutions for eliminating these deficiencies that will result inconveniences have been tried to reveal.